The Commuting Distribution - Jos van Ommeren (Tinbergen Institute, 2004)
In this paper we analyse the commuting distribution from a job search perspective.We have examined under which conditions the commuting distribution is unimodal which isone of the stylised facts of commuting. It appears that a necessary condition is that space istwo-dimensional. Furthermore, one of the following ingredients is sufficient: on-the-jobmobility, spatially-differentiated search or heterogeneity ofjobs. Residential mobility does notappear to explain the shape of the commuting density function as we observe it.
Keywords: R20; J64; 330; commuting; search; mobility; Arbeitsuche; Wohnstandort; Pendelverkehr